2016
DOI: 10.1167/iovs.15-18753
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Neovascular Lesion Hyperreflectivity After Anti-VEGF Treatment in Age-Related Macular Degeneration: An Integrated Multimodal Imaging Analysis

Abstract: Citation: Casalino G, Bandello F, Chakravarthy U. Changes in neovascular lesion hyperreflectivity after anti-VEGF treatment in age-related macular degeneration: an integrated multimodal imaging analysis. Invest Ophthalmol Vis Sci. 2016;57:OCT288-OCT298. DOI:10.1167/iovs.15-18753 PURPOSE. To correlate presence of hyperreflective material (HRM) on spectral-domain optical coherence tomography (SD-OCT) with color fundus photography (CFP) in patients with different subtypes of neovascular age-related macular deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 25 publications
4
50
0
Order By: Relevance
“…In our series, increasing SHRM thickness, when centre‐involving, adversely impacted VA in the linear regression. Thickness and texture of SHRM on OCT have previously been shown to affect visual prognosis . Casalino et al .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In our series, increasing SHRM thickness, when centre‐involving, adversely impacted VA in the linear regression. Thickness and texture of SHRM on OCT have previously been shown to affect visual prognosis . Casalino et al .…”
Section: Discussionsupporting
confidence: 89%
“…The well‐defined variant of SHRM was exclusively observed in our case series and more likely represents organized, fibrotic tissue. This supports the observation that anti‐VEGF treatment induces a maturation of neovascular complexes towards an organized tissue in which hyper‐reflectivity increases over time …”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…[31,32] The first retinal layer to be affected by breakdown of the outer blood-retinal barrier is the OPS layer as well as the neighboring ellipsoid zone, which is also referred as the photoreceptor inner segment/outer segment (IS/OS) layer. Accumulation of subretinal fluid leads to detachment of the neurosensory retina and functional impairment of the photoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that fluid from the active CNV resulted in the alteration of the optical reflectivity at the CNV margin, eventually leading to an obscure and fuzzy appearance, despite the lack of an apparent fluid space on OCT. Another possibility is the role of fibrin on the appearance of ill-defined subretinal hyper-reflective material. A recent study by Casalino et al 22 suggested that ill-defined hyper-reflective material seen in patients with neovascular AMD is correlated with fibrin on FP, and that the border of hyper-reflective material became much clearer after receiving anti-VEGF treatment. Using OCT, our study has provided additional guidelines for the treatment of myopic CNV, and that the fuzzy margin of the myopic CNV lesion on OCT examination was significantly correlated with active leakage on FA.…”
Section: Discussionmentioning
confidence: 99%